Digital storytelling : an introduction / Leah Henrickson. - Henrickson, Leah (Polity, 2025)
Storytelling is part of who we are and, with digital media it's more accessible and adaptable than it has ever been. Since emerging in the 1990s, the field of digital storytelling has centred on a single model of story creation that remains in widespread use today. However, digital media, environments, and communities have changed. It's time for the field of digital storytelling to change with them. This book provides a cutting-edge introduction to this topic. In doing so, it sets an alternative agenda for the field: one that regards digital storytelling as characterised not by any particular kind of method or output, but by ongoing processes of meaning-making in digital environments. Weaving historical references throughout, this textbook illustrates the interconnectedness of media, individual experiences, and society and culture.